Answer:
Explanation contains answer.
Step-by-step explanation:
Question 1:
I would perfer to solve the first equation for y because there is only one operation to perform on both sides and it is subtraction of 2x on both sides.
The other equation requires two steps to isolate y; subtracting 3x on both sides then multiplying both sides by -1.
So basically solving the first one for y because it has coefficient 1.
Question 2:
They solved the 2nd equation for y and plugged into itself instead of plugging it into 1st equation.
ali and jake went on a cross country trip they took a train part of the way and took a bus the rest of the way they traveled a total of 1450 riding on the train 150 more kilometers than on the bus
let x=kilometers traveled by bus
let y = kilometers traveled by train
question how many kilometers did they travel by train?
Answer:
=800 km
Step-by-step explanation:
Let the distance traveled by train be y and by bus be x.
Bus -x
Train -y
y=x+150 (since they traveled by train for a distance of 150 km more than by bus.)
The sum of the two is equal to 1450
x+y=1450
y=x+150
These two form simultaneous equations.
y+x=1450..............i
y-x=150.................ii
Adding ii to i gives:
2y=1600
Divide both sides by two
y=800
Distance traveled by train =y=800 km
Answer:
800
Step-by-step explanation:
help with 1-6 , please !!!!!
Answer:
sum of angles of triamgle is 180 degree
the half base× hight ue1/2×b×h
use the formula for all qusetions
Need answer to A and B!
To find the probability of drawing certain colour of balls, we first need to find the total number of balls:
5 + 7 +5 = 17
For the number of red balls that need to be added
The original probability of drawing a red ball:
red ball/ total number of balls
= 5/17
To find the number of balls required, we can set an equation.
Let the number of red balls that need to be added be x.
5+x / 17+x = 5/6
(5+x) x 6 = (17+ x) x5
30 + 6x = 85 + 5x
6x - 5x = 85 - 30
x = 55
Therefore, 55 red balls need to be added.
For the number of black balls that need to be added
The original probability of drawing a white ball:
white ball/ total number of balls
=5/17
To find the probability required, we can set an equation.
Let the number of black balls that need to be added be y.
5/ 17 + y = 1/6
5 x 6 = 17 + y
30 = 17 + y
30 - 17 = y
y = 13
Therefore, 13 black balls need to be added.
Hope it helps!
Write an equation for a rational function with:
Vertical asymptotes of x = 2 and x = -3
x intercepts of (-6,0) and (3,0)
Horizontal asymptote of y = 6
Use y as your output variable.
Answer:
y=(6(x+6)(x-3))/((x-2)(x+3))
Step-by-step explanation:
The vertical asymptote should be in the denominator. The x-interceps should be in the numerator. Because we have horizontal asymptote y=6, then we have to put 6 in the numerator. the horizontal asymptote is the leading coefficient of the numerator ÷ the leading coefficient of the denominator, when the degree of the numerator and denominator are the same.
Given the horizontal asymptote, vertical asymptotes and x intercepts, the equation of the rational function is y = 6((x+6)(x-3))/((x-2)(x+3)). The vertical asymptotes are found by setting the function's denominator equal to zero, while the x-intercepts come from setting the numerator to zero.
Explanation:In this question, we are asked to write the equation of a rational function based on given conditions. The function's vertical asymptotes are located at x = 2 and x = -3, and has x-intercepts at (-6,0) and (3,0), with a horizontal asymptote at y = 6.
The general form of a rational function is y = (ax+b)/(cx+d). Asymptotes help define the behavior and boundaries of the function. In this situation, we can set the denominator of our function equal to zero to find our vertical asymptotes, giving us (x-2)(x+3). To achieve our stated x-intercepts, we set the numerator equal to zero, providing (x+6)(x-3). Combining these, the function becomes y = ((x+6)(x-3))/((x-2)(x+3)). The output of the function approaches the horizontal asymptote as x approaches infinity. Thus to have y = 6 as our horizontal asymptote, we adjust our function to maintain this behaviour, settling on y = 6((x+6)(x-3))/((x-2)(x+3)).
Learn more about Rational Function here:https://brainly.com/question/35067519
#SPJ11
After graduating from college, Carlos receives two different job offers. Both pay a starting salary of
$62000 one job promises a $3720 raise per year. What will the salary be in one year
Answer:
$65720
Step-by-step explanation:
The job pays a starting salary of $62000, and raises $3720 per year. In one year, Carlos will be earning $62000 + $3720 = $65720
Final answer:
Carlos's salary in one year will be $65720, which is the sum of his starting salary, $62000, and the promised annual raise of $3720.
Explanation:
After graduating from college, Carlos has received two different job offers, both offering a starting salary of $62000, and one includes a promise of a $3720 raise per year. To calculate his salary in one year, we need to add this annual raise to his starting salary.
Starting salary: $62000
Raise after one year: $3720
Carlos's salary in one year: $62000 + $3720 = $65720
This computation shows that with the promised annual raise, Carlos's salary for the next year would be $65720.
The value of x is?
84
96
132
264
HELPPPP!!!!
Answer:
x =96 degree.
Step-by-step explanation:
Given : Triangle .
To find : The value of x is
Solution : We have given triangle
Exterior Angle sum property of triangle : Sum of all exterior angle of triangle is 360.
130 + 134 + x = 360 .
264 + x = 360.
On subtracting both sides by 264 .
x = 360 - 264 .
x = 96.
Therefore, x =96 degree.
Using Exterior Angle sum property of the triangle, The value of x will be 96 degree.
What is the Exterior Angle sum property?Exterior Angle sum property of the triangle states that the Sum of all exterior angles of the triangle is 360.
Given: Two exterior angles measure of 130 and 134 degrees.
To find: The value of x is
So,
130 + 134 + x = 360 .
264 + x = 360.
x = 360 - 264 .
x = 96.
Using Exterior Angle sum property of the triangle, The value of x will be 96 degrees.
Learn more about angles here;
https://brainly.com/question/13954458
#SPJ5
what are the zeros of the polynomial function f(x)=x^3-x^2-6x
Answer:
x = -2, x = 0, and x = 3
Step-by-step explanation:
it was right lol
Factor each expression. Show your work. 11. r2 + 12r + 27 12. g2 – 9 13. 2p3 + 6p2 + 3p + 9
Answer:
11. r^2 + 12r + 27 = (r+3)(r+9)
12. g^2-9 = (g+3)(g-3)
13. 2p^3 + 6p^2 + 3p + 9 = (2p^2+3)(p+3)
Step-by-step explanation:
[tex]11.\ r^2 + 12r + 27\\Factorizing\\= r^2+9r+3r+27\\=r(r+9)+3(r+9)\\=(r+3)(r+9)\\\\12. g^2-9\\The\ expression\ will\ be\ factorized\ using\ the\ formula\\(a+b)(a-b)=a^2-b^2\\So,\\g^2-9\\=(g)^2-(3)^2\\=(g+3)(g-3)\\\\13. 2p^3 + 6p^2 + 3p + 9\\=2p^2(p+3)+3(p+3)\\=(2p^2+3)(p+3)[/tex] ..
Which of the following would be the most logical first step to solving this
quadratic equation?
2x2-x+ 2 = -11
O
A. Divide both sides by x.
O
B. Take the square root of both sides.
O
C. Set up smaller equations using the zero product rule.
O
D. Add 11 to both sides.
Answer:
D is correct option
Step-by-step explanation:
The correct option is D.
The standard quadratic equation is ax²+bx+c=0
Where a and b are coefficients and c is constant.
It means that constant are on the L.H.S and there is 0 on the right hand side.
Therefore to make it a quadratic equation first of all you have to add 11 at both sides so that the R.H.S becomes 0.
The given equation is:
2x2-x+ 2 = -11
If we add 11 on both sides the equation will be:
2x2-x+ 2 +11= -11+11
2x^2-x+13=0
Thus the correct option is D
You can further solve it by applying quadratic formula....
Final answer:
The most logical first step to solve the quadratic equation 2x² - x + 2 = -11 is to set up smaller equations using the zero product rule and then applthe quadratic formula. The correct option is c.
Explanation:
The most logical first step to solve the quadratic equation 2x² - x + 2 = -11 is to:
C. Set up smaller equations using the zero product rule.
Once the equation is rearranged, apply the quadratic formula to determine the values of x.
Using the quadratic formula yields the solutions by substituting the values of a, b, and c correctly.
¿Cuál de las siguientes funciones es una función constante? a. Y=x+1 b. Y=x+2 c. X=y+3 d. Y=3
Answer:
Option D y=3
Step-by-step explanation:
The question in English is
Which of the following functions is a constant function?
we know that
A constant function is a function whose output value is the same for every input value
so
Verify each case
case A) y=x+1
This is not a constant function, this is a linear equation
Is a function whose output value is different for every input value
case B) y=x+2
This is not a constant function, this is a linear equation
Is a function whose output value is different for every input value
case C) x=y+3
This is not a constant function, this is a linear equation
Is a function whose output value is different for every input value
case D) y=3
This is a constant function
Is a function whose output value is the same for every input value
which geometric object is defined as the set of ballpoints in a plane at a given distance A.Parabole B. Line segment C. Line D. circle
Answer:
Answer is Circle
Step-by-step explanation:
Check the picture below.
notice, all points are equidistant from the center of it, wherever the center happens to be.
Expand and simplify (X+5)(X+1)
Answer:
Step-by-step explanation:
(X+5)(X+1) = x²+x+5x+5 = x² +6x+5
(X+5)(X+1)
Use the FOIL method to expand.
This means multiply each term in the first set of parenthesis by each term in the second set.
x *x = x^2
x*1 = x
5*x = 5x
5*1 = 5
Now you have x^2 + x + 5x + 5
Now simplify by combining like terms:
x^2 + 6x + 5
Which of the following equations is of a parabola with a vertex at (0,3)?
y= (x - 3)2
y= (x + 3) 2
y=x2-3
y= x2 + 3
Answer:
[tex]y=x^{2}+3[/tex]
Step-by-step explanation:
we know that
The equation of a vertical parabola in vertex form is equal to
[tex]y=a(x-h)^{2}+k[/tex]
where
(h,k) is the vertex
In this problem we have the vertex at point (0,3)
substitute
[tex]y=a(x-0)^{2}+3[/tex]
[tex]y=ax^{2}+3[/tex]
therefore
The option [tex]y=x^{2}+3[/tex] is the answer
In this case the coefficient a is equal to 1
If f(x) = 3х – 15, what is f(4)?
[tex]\huge{\boxed{f(4)=\bf{-3}}}[/tex]
In this case, you are replacing all instances of [tex]x[/tex] with [tex]4[/tex]. [tex]f(4)=3(4)-15[/tex]
Multiply. [tex]f(4)=12-15[/tex]
Subtract. [tex]f(4)=-3[/tex]
find the length of arc JM
Answer:
JM ≈ 12.9 miles
Step-by-step explanation:
The length of the arc is calculated as
arc = circumference × fraction of circle
= πd × [tex]\frac{90}{360}[/tex]
JM = π × 16.4 × [tex]\frac{1}{4}[/tex]
= [tex]\frac{16.4\pi }{4}[/tex] ≈ 12.9
The length of the arc JM will be 12.88 miles.
What is the arc length of the sector?Let r is the radius of the sector and θ be the angle subtends by the sector at the center. Then the arc length of the sector of the circle will be
Arc = (θ/360) 2πr
The diameter is 16.4 miles. Then the radius will be
r = d / 2
r = 16.4 / 2
r = 8.2 miles.
And angle (θ) will be 90 degrees.
Then the length of the arc JM will be
Arc = (90/360) 2π x 8.2
Arc = 12.88 miles
More about the arc length of the sector link is given below.
https://brainly.com/question/15955580
#SPJ2
what is the slope intercept equation of the line below
Answer:
y=2x-3
Step-by-step explanation:
The slope-intercept form of a linear equation is y=mx+b where m is the slope and b is the y-intercept.
The y-intercept is where it crosses the y-axis. It cross the y-axis in your picture at -3 so b=-3.
Now the slope=rise/run. So starting at (0,-3) we need to find another point that crosses nicely on the cross-hairs and count the rise to and then the run to it. So I see (1,-1) laying nicely. So the rise is 2 and the run is 1.
If you don't like counting. You could just use the slope formula since we already identified the two points as (-1,1) and (0,-3).
The way I like to use the formula is line up the points and subtract vertically then put 2nd difference over 1st difference.
(0,-3)
-(1,-1)
----------
-1 -2
So the slope is -2/-1 or just 2.
We have that m is 2 and b is -3.
Plug them into y=mx+b and you are done.
y=2x-3.
Slope intercept equation of the line is y = 2x - 3.
What is slope-intercept form?Slope intercept form gives the graph of a straight line and is represented in the form of y=mx + c.
By checking the graph by drawing manually.
From that we get the equation
y = 2x - 3
Comparing above equation with the standard slope-intercept form y = mx +c, we get
Slope : m = 2
Now, given equation can be re-written as :
2x - y = 3
Divide by 3 on both sides
[tex]\frac{2x}{3} -\frac{y}{3} =\frac{3}{3}[/tex]
[tex]\frac{x}{\frac{3}{2} } -\frac{y}{3} =1[/tex]
Comparing above equation with intercept form:
[tex]\frac{x}{a}+\frac{y}{b}=1[/tex], we get
x-intercept : [tex]a=\frac{3}{2}[/tex]
y-intercept : [tex]b=-3[/tex]
Now the given straight line intersects the coordinate axes at [tex](\frac{3}{2} ,0)[/tex] and [tex](0,-3)[/tex]. Specify these plots on XY-plane & join by a straight line to get a plot.
Find out more information about slope-intercept form here
https://brainly.com/question/9682526
#SPJ2
PLEASE HELP AND ANSWER!!!!! Which of the following reveals the minimum value for the equation 2x2 + 12x − 14 = 0?
2(x + 6)2 = 26
2(x + 6)2 = 20
2(x + 3)2 = 32
2(x + 3)2 = 30
Answer:
The correct option is 3.
Step-by-step explanation:
The given equation is
[tex]2x^2+12x-14=0[/tex]
It can be written as
[tex](2x^2+12x)-14=0[/tex]
Taking out the common factor form the parenthesis.
[tex]2(x^2+6x)-14=0[/tex]
If an expression is defined as [tex]x^2+bx[/tex] then we add [tex](\frac{b}{2})^2[/tex] to make it perfect square.
In the above equation b=6.
Add and subtract 3^2 in the parenthesis.
[tex]2(x^2+6x+3^2-3^2)-14=0[/tex]
[tex]2(x^2+6x+3^2)-2(3^2)-14=0[/tex]
[tex]2(x+3)^2-18-14=0[/tex]
[tex]2(x+3)^2-32=0[/tex] .... (1)
Add 32 on both sides.
[tex]2(x+3)^2=32[/tex]
The vertex from of a parabola is
[tex]p(x)=a(x-h)^2+k[/tex] .... (2)
If a>0, then k is minimum value at x=h.
From (1) and (2) in is clear that a=2, h=-3 and k=-32. It means the minimum value is -32 at x=-3.
The equation [tex]2(x+3)^2=32[/tex] reveals the minimum value for the given equation.
Therefore the correct option is 3.
The correct answer is option 3. [tex]2(x + 3)^2 = 32[/tex].
To find the minimum value of the quadratic equation [tex]2x^2 + 12x - 14[/tex] = 0, we can rewrite it in vertex form, which reveals the minimum or maximum value of a quadratic function.
The given options are attempts at rewriting the quadratic equation in vertex form. Let’s rewrite the equation:
First, complete the square:
1. Start with the equation: [tex]2x^2 + 12x - 14[/tex]
2. Factor out the coefficient of x² from the first two terms: [tex]2(x^2 + 6x) - 14[/tex]
3. Complete the square inside the parentheses:
- Take [tex](\frac{6}{2})^2 =9[/tex] - Add and subtract 9 inside the parentheses: [tex]2(x^2 + 6x + 9 - 9) - 14[/tex]
- Simplify inside the square: [tex]2((x + 3)^2 - 9) - 14[/tex]
4. Distribute and simplify: [tex]2(x + 3)^2 - 18 - 14 = 2(x + 3)^2 - 32[/tex]
Comparing this with the options, we have [tex]2(x + 3)^2 = 32[/tex].
The correct answer is: [tex]2(x + 3)^2 = 32[/tex].
The volume of the spheres is 500/3 pie cubic units What is the value of X?
Answer:
125
Step-by-step explanation:
500 ÷ 4 = 125
I think this is the right answer. sorry if I'm wrong.
Answer:
x=5 assuming that x is the radius.
x is the radius?
Step-by-step explanation:
[tex]V=\frac{4}{3} \pi r^3[/tex] is the volume of a sphere.
We are given [tex]V=\frac{500}{3} \pi[/tex] cubic units.
We are asked to find the value of x. If x is not the radius, please correct me:
[tex]V=\frac{4}{3}\pi r^3[/tex] with [tex]V=\frac{500}{3} \pi[/tex] and the assumption that x is r.
[tex]\frac{500}{3}\pi=\frac{4}{3}\pi x^3[/tex]
If you multiply both sides by 3, then you would have:
[tex]500 \pi=4 \pi x^3[/tex]
If you divide both sides by [tex]\pi[/tex] you will have:
[tex]500=4x^3[/tex]
If you divide both sides by 4, you will have:
[tex]125=x^3[/tex]
The last step would be to take the cube root of both sides:
[tex]\sqrt[3]{125}=x[/tex]
[tex]5=x[/tex]
[tex]x=5[/tex]
If point P is 4/7 of the distance from M to N, what ratio does the point P partition the directed line segment from M to N into?
4:1
4:3
4:7
4:10
Answer:
4:3
Step-by-step explanation:
Given that P divides segment MN into 4/7, let MN to be x units in length then
MP = 4/7 x =4x/7 --------(i)
But MN =MP+PN so;
x=4x/7 +PN
x- 4X/7 =PN
3x/7 =PN ----------(ii)
To get the ratio of MP:PN
MP: PN
4x/7:3x/7
MP/PN = 4x/7 / 3x/7
MP/PN =4/3
MP:PN = 4:3
Answer: 4:3
Step-by-step explanation:
Given : A point P is 4/7 of the distance from M to N.
∴ Let the distance between M to N be d.
[tex]\Rightarrow\ MP=\dfrac{4}{7}\times d=\dfrac{4d}{7}[/tex]
Also, the point P partition the directed line segment from M to N .
Thus , MN = MP+PN
[tex]\Rightarrow\ d=\dfrac{4d}{7}+PN\\\\\Rightarrow\ PN= d-\dfrac{4d}{7}=\dfrac{7d-4d}{7}\\\\\Rightarrow\ PN=\dfrac{3}{7}d[/tex]
Now, the ration of MP to PN will be :-
[tex]\dfrac{MP}{PN}=\dfrac{\dfrac{4d}{7}}{\dfrac{3d}{7}}=\dfrac{4}{3}[/tex]
∴ Point P partitioned the line segment MN into 4:3.
Write 0.68as a fraction in the lowest terms.
Answer:
17/25
Step-by-step explanation:
First, convert the decimal into a fraction. To do so, move the decimal point to the right two place values and place over 100.
0.68 = 68/100
Next, simplify. Divide common factors. Remember, what you do to one side, you do to the other. Divide 4 from both sides:
(68/100)/4 = (17/25)
17/25 is your answer.
~
0.68 can be expressed as the fraction 17/25 in the lowest terms.
A fraction in its lowest termStep 1: Let x be the decimal representation of the fraction.
x = 0.68
Step 2: Since there are two digits after the decimal point, we can multiply both sides of the equation by 100 to eliminate the decimal.
100x = 68
Step 3: Simplify the fraction by dividing both the numerator and denominator by their greatest common divisor (GCD), which in this case is 4.
100 ÷ 4 = 25
68 ÷ 4 = 17
The simplified fraction is:
0.68 = 17/25
Therefore, 0.68 can be expressed as the fraction 17/25 in the lowest terms.
More on lowest-term fractions can be found here: https://brainly.com/question/29156749
#SPJ6
PLEASE HELP ASAP If mZYWZ - 17, what is mw
?
34
73
56
17
Answer:
73°
Step-by-step explanation:
Since WX = WZ then ΔWXZ is isosceles and WY is perpendicular to XZ
Hence ∠XYW = 90°
YW bisects XWZ, hence ⇒ ∠ YWX = ∠YWZ = 17°
The sum of the 3 angles in ΔWXY = 180°, hence
∠WXY = 180° - (90 + 17)° = 180° - 107° = 73°
Sara bought a soft drink for four dollars and five candy bars. She spent a total of nineteen
dollars. How much did each candy bar cost?
Answer:
The cost of each candy bar is $3....
Step-by-step explanation:
Let:
x= $4 (soft drink)
z= price of each candy bar
y=5z(Total price of 5 candy bars)
C= $19(spent money)
The equation is:
C= x+y
$19=$4+5z
Subtract 4 from both sides:
$15=5z
Divide both sides by 5
z=$3
Hence the cost of each candy bar is $3....
Determine algebraically whether f(x) = x^2(x^2 + 9)(x^3 + 2x) is even or odd.
[tex]f(x) = x^2(x^2 + 9)(x^3 + 2x)\\\\f(-x) = (-x)^2((-x)^2 + 9)((-x)^3 + 2\cdot(-x))\\f(-x)=x^2(x^2+9)(-x^3-2x)\\f(-x)=-x^2(x^2+9)(x^3+2x)\\\Large f(-x)\not =f(x)\implies\text{not even}\\\\-f(x)=-x^2(x^2+9)(x^3+2x)\\ -f(x)=f(-x)\implies \text{odd}[/tex]
Complete the table for the given rule y=x-3
For the first row, where x is equal to 7, to find y plug 7 in for x like so...
y = 7 - 3
y = 4
For the second row, where y is equal to 1, to find x plug 1 in for y like so...
1 = x - 3
To solve for x add 3 to both sides. This will cancel 3 from the right side:
1 + 3 = x - 3 + 3
4 = x + 0
x = 4
For the third row, where y is equal to 7, to find x plug 7 in for y like so...
7 = x - 3
To solve for x add 3 to both sides. This will cancel 3 from the right side:
7 + 3 = x - 3 + 3
10 = x + 0
x = 10
First row: y is 4
Second row: x is 4
Third row: x is 10
Hope this helped!
~Just a girl in love with Shawn Mendes
Which of the equations below can be used to find the measure of ∠A?
A. A2=6.7^2+9.4^2
B. cosA=6.7/9.4
C. tanA=9.4/6.7
D. sinA/9.4=sin90/6.7
Answer:
I believe the answer is C.
The trigonometric function gives the ratio of different sides of a right-angle triangle. The correct option is C.
What are Trigonometric functions?The trigonometric function gives the ratio of different sides of a right-angle triangle.
[tex]\rm Sin \theta=\dfrac{Perpendicular}{Hypotenuse}\\\\\\Cos \theta=\dfrac{Base}{Hypotenuse}\\\\\\Tan \theta=\dfrac{Perpendicular}{Base}[/tex]
where perpendicular is the side of the triangle which is opposite to the angle, and the hypotenuse is the longest side of the triangle which is opposite to the 90° angle.
To find the measure of angle A, we need to use the tangent trigonometric function this is because except for the hypotenuse of the triangle the other two sides of the equation are known.
Therefore, the equation of the tangent function of trigonometry for angle A can be written as,
tan(A) = Perpendicular /Base
tan(A) = 9.4 / 6.7
Hence, the equations below that can be used to find the measure of ∠A is tanA=9.4/6.7.
Learn more about Trigonometric functions:
https://brainly.com/question/6904750
#SPJ5
Solve the equation over the interval [0,2pi) 4cscx + 6= -2
[tex]\bf 4csc(x)+6=-2\implies 4csc(x)=-8\implies csc(x)=\cfrac{-8}{4}\implies csc(x)=-2 \\\\\\ \cfrac{1}{sin(x)}=-2\implies \cfrac{1}{-2}=sin(x)\implies sin^{-1}\left( -\cfrac{1}{2} \right)=x\implies x= \begin{cases} \frac{7\pi }{6}\\\\ \frac{11\pi }{6} \end{cases}[/tex]
Find the slope of the line that passes through the points (-1, 1) and (2, 7).
Answer:
2 is your slope
Step-by-step explanation:
Find the slope. Use the slope-formula:
m (slope) = (y₂ - y₁)/(x₂ - x₁)
Let:
(x₁ , y₁) = (-1 , 1)
(x₂ , y₂) = (2 , 7)
Plug in the corresponding numbers to the corresponding variables:
m = (7 - 1)/(2 - (-1))
Simplify:
m = (6)/(2 + 1)
m = 6/3
m = 2
2 is your slope (or rise 2, run 1).
~
Answer:
slope = 2
Step-by-step explanation:
Calculate the slope m using the slope formula
m = (y₂ - y₁ ) / (x₂ - x₁ )
with (x₁, y₁ ) = (- 1, 1) and (x₂, y₂ ) = (2, 7)
m = [tex]\frac{7-1}{2+1}[/tex] = [tex]\frac{6}{3}[/tex] = 2
The radius, diameter, or circumference of a circle is given. Find the missing measures. Round to the nearest hundredth if necessary. r = 7.8 mm, d = ? , C = ? Question 1 options: d = 15.6 mm, C = 24.50 mm d = 15.6 mm, C = 49.01 mm d = 3.9 mm, C = 49.01 mm d = 3.9 mm, C = 24.50 mm
Answer:
Second option:
[tex]d = 15.6\ mm,\ C = 49.01\ mm[/tex]
Step-by-step explanation:
We can observe that the radius of the circle is given. This is:
[tex]r = 7.8\ mm[/tex]
And the missing measures are the diameter of the circle and the circumference.
Since the diameter of a circle is twice the radius, we get that this is:
[tex]d=2r\\\\d=2(7.8\ mm)\\\\d=15.6\ mm[/tex]
To find the circumference of the circle, we can use this formula:
[tex]C=2\pi r[/tex]
Where "r" is the radius of the circle.
Substituting the radius into the formula, we get:
[tex]C=2\pi r\\\\C=2\pi (7.8\ mm)\\\\C=49.01\ mm[/tex]
The original price of a skateboard was reduced by $15. The new price is $49.
Answer:
The original price of a skateboard is $64
Step-by-step explanation:
Let
x ----> the original price of a skateboard
y ----> the new price of a skateboard
we know that
The linear equation that represent this problem is equal to
y=x-15 ----> equation A
y=49 ---> equation B
substitute equation B in equation A and solve for x
49=x-15
Adds 15 both sides
49+15=x
64=x
Rewrite
x=$64
If g(x) = xsquared +2, find the g (3)
Answer:
g(3)=11 I think
Step-by-step explanation:
Since x is 3, you substitute it in for the x. So it would be 3 squared +2.
I'm not sure if this is right but I tried helping.
Answer:
g(3) =11
Step-by-step explanation:
g(x) = x^2 +2
Let x =3
g(3) = 3^2 +2
= 9+2
= 11